Functions of film images of Warsaw in the Polish cinema of the 1960s - Zwierzchowski, Piotr (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2019)
Polish cinema of the 1960s presented a specific vision of Warsaw, different from earlier and later ones, although it contained some solid motifs for the entire PRL era. These include emphasizing the uniqueness of Warsaw, the war past as an inseparable part of the city’s identity (though in the 1960s with a slightly different meaning) or the problem of getting a flat. The separateness and specificity of the then created images of the capital was related to the political specificity of the decade, the cultural and social moment of Warsaw development, the domination of realism that made the message authentic and genological issues – the main role in creating the image of the city was played by comedy. These images, however, were sometimes surprisingly subversive, breaking the dominant image.